Nomenclatural changes in North American Phymatodes Mulsant (Coleoptera: Cerambycidae) - Swift, Ian P.; Ray, Ann M. (Zootaxa, 2010)
The following nomenclatural changes to the genus Phymatodes Mulsant, 1839 are proposed: P. juglandis Leng, 1890 = P. decussatus (LeConte, 1857); P. mohavensis Linsley and Chemsak, 1963 = P. nitidus LeConte, 1874; P. lecontei Linsley, 1938 (a replacement name) = P. grandis Casey, 1912; P. oregonensis Chemsak, 1963 = P. nigrescens Hardy and Preece, 1927; P. blandus picipes Linsley, 1934 and P. blandus propinquus Linsley, 1934 = P. blandus (LeConte, 1859); P. hirtellus densipennis Casey, 1912 and P. ursae Knull, 1940 = P. hirtellus (LeConte, 1873); P. decussatus australis Chemsak, 1963 and P. decussatus posticus Van Dyke, 1920 = P. obliquus Casey, 1891; P. frosti Casey, 1924, a valid name which has not previously been mentioned in the literature = P. dimidiatus (Kirby in Richardson, 1837); P. concolor Linsley, 1934 is afforded full species status; P. lividus (Rossi, 1794) is formally recorded as established in North America. A key and diagnoses for all native and introduced North American species are provided, which include the more recently described species, P. tysoni Linsley and Chemsak, 1984, and P. shareeae Cope, 1984, in addition to the introduced species P. lividus.